FAKTOR PENDORONG DAN PENGHAMBAT RANTAI PASOKAN RAMAH LINGKUNGAN: LITERATUR REVIEW - Anjar Priyono (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2008)
This paper discusses the implementation of green supply chain management in manufacturing industry. Majority of manufacturing companies adopt these practices partially in certain function of organization. This paper describes integration of the whole organization function in the GSCM. Each part plays different role using different methods and techniques. Several elements involved in the product flows are inbound logistic, production function, outbound logistic, and reverse logistic. The last function will be described in detailed explanation since such function is still relatively new. Discussion not only describes the advantage of GSCM implementation but also barriers to implement GSCM. Besides, various cost related to such practices will also be discussed because over cost will have potential negative effect to organization performance. In the last section, controversial issues related to GSCM will be discussed especially how these practices effects organizational performance, how to implement these program in small and medium business, and how the program effect customer preference and customer satisfaction.Key words: supply chain management, inbound logistic, production function, outbound logistic and reverse logistic.